Metagenome-assembled genomes from mineral tundra soils in Rásttigáisá, northern Norway - Pessi, Igor S; Rutanen, Aino; Hultman, Jenni (Microbiology Society, 2025)
Microbial communities in tundra soils remain largely unknown despite their important roles in the cycling of greenhouse gases. Here, we report 59 non-redundant metagenome-assembled genomes (MAGs) recovered from mineral tundra soils in Rásttigáisá, northern Norway. The MAGs were obtained by clustering contigs according to tetranucleotide frequency and differential coverage and were manually curated to remove contigs with outlying GC content and/or mean coverage. Most MAGs were assigned to the bacterial phyla Candidatus Dormibacterota (n=12), Verrucomicrobiota (n=10), and Acidobacteriota (n=9). All archaeal MAGs (n=4) belong to the genus Candidatus Nitrosopolaris (phylum Thermoproteota). The 59 Rásttigáisá MAGs expand our knowledge of the diversity and ecological roles of tundra microbiomes.